Objective indicators of large-scale food shortages? Some remarks on their purpose and limitations - Winfried Urff; Heinz Ahrens (Intereconomics, 1981)
In the past, a rather late realization of acute and large-scale food shortages often contributed to insufficient preventive or remedial action. Against this backround a Working Party set up by the FAO Committee on World Food Security has suggested a number of “objective indicators” which are hoped to enable the FAO to make a rapid preliminary judgment of the overall food situation and of the nature of food shortages. Are these hopes justified?
Keywords: 330; Food Security